2020
DOI: 10.1007/s12325-020-01354-6
|View full text |Cite
|
Sign up to set email alerts
|

Limited Utility for Benzodiazepines in Chronic Pain Management: A Narrative Review

Abstract: Introduction: Controversy and uncertainty exist about the use of benzodiazepine receptor agonists (BZRAs) in pain management. This article curates available research to determine the appropriate role of BZRAs in the course of pain management, and how prescribers might address these challenges. Methods: A narrative review was performed to determine the appropriate role of BZRAs in pain management and to develop practice recommendations. Publications were identified by a search of PubMed, references of retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 134 publications
0
17
0
1
Order By: Relevance
“…24 28 Although early research suggested BZDs had a direct analgesic effect related to central or peripheral receptormediated interactions, 24 29 there has not been conclusive evidence that BZDs produce an overall analgesic effect. 22 Accordingly, researchers have proposed that benefits related to pain management could result from BZDs alleviating pain-related anxiety and/or depression. 27 Adverse effects of BZDs include sedation, addiction 7 and increased risk of suicide.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…24 28 Although early research suggested BZDs had a direct analgesic effect related to central or peripheral receptormediated interactions, 24 29 there has not been conclusive evidence that BZDs produce an overall analgesic effect. 22 Accordingly, researchers have proposed that benefits related to pain management could result from BZDs alleviating pain-related anxiety and/or depression. 27 Adverse effects of BZDs include sedation, addiction 7 and increased risk of suicide.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Sleep disorders and pain cause a vicious spiral and should be treated simultaneously in clinical situations. Common sleep drugs, benzodiazepines, and nonbenzodiazepines (also referred to as Z-drugs) have a narrow role in managing secondary sleep disorders caused by other mental or physical conditions, including pain [13]. Furthermore, the indications for these drugs should be limited due to their harmful side effects, such as falling [14], cognitive impairment [15], dependence [16], and increased risk of death [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, although benzodiazepines are frequently indicated for clinical treatment of pain-induced anxiety, their clinical use with analgesic intent is still controversial [55,56]. Here, we found that systemic injection of midazolam brought back the anxiety behavior of CNC group to CS levels.…”
Section: Discussionmentioning
confidence: 67%